2022
DOI: 10.1021/jacs.2c00724
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Guanine Crystals Are Solid Solutions of Guanine and Other Purine Metabolites

Abstract: Highly reflective crystals of the nucleotide base guanine are widely distributed in animal coloration and visual systems. Organisms precisely control the morphology and organization of the crystals to optimize different optical effects, but little is known about how this is achieved. Here we examine a fundamental question that has remained unanswered after over 100 years of research on guanine: what are the crystals made of ? Using solution-state and solid-state chemical techniques coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 67 publications
8
75
0
Order By: Relevance
“…At least nine distinct guanine morphologies are known, [ 18 ] including irregular [ 16,19 ] and regular hexagonal plates, [ 5 ] square plates, [ 8 ] irregular polygons, [ 16,20,21 ] and prisms. [ 15,16 ] In these crystals, the thermodynamically disfavoured (100) face (parallel to the high refractive index H‐bonded plane), is preferentially expressed and often oriented toward the incident light, maximizing reflection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least nine distinct guanine morphologies are known, [ 18 ] including irregular [ 16,19 ] and regular hexagonal plates, [ 5 ] square plates, [ 8 ] irregular polygons, [ 16,20,21 ] and prisms. [ 15,16 ] In these crystals, the thermodynamically disfavoured (100) face (parallel to the high refractive index H‐bonded plane), is preferentially expressed and often oriented toward the incident light, maximizing reflection.…”
Section: Introductionmentioning
confidence: 99%
“…[13] By precisely controlling the morphology and superstructural organization of the crystals, organisms tune the type of optical effect produced from multilayer inter ference [5,14] and diffuse scattering [6,15,16] to reflection from 3D-photonic crystals. [17] At least nine distinct guanine morphologies are known, [18] including irregular [16,19] and regular hexagonal plates, [5] square plates, [8] irregular polygons, [16,20,21] and prisms. [15,16] In these crystals, the thermodynamically disfavoured (100) face (parallel to the high refractive index H-bonded plane), is preferentially expressed and often oriented toward the incident light, maximizing reflection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at around 123 ppm also appears in the ss-NMR spectrum of the raw pure hypoxanthine that consists of N 9 -hypoxanthine. 41 Considering the above results mentioned, we concluded that the doping forms of hypoxanthine in AG β and AG α are N 7 -hypoxanthine, and in GM are N 9 -hypoxanthine. We propose that guanine and hypoxanthine formed various solid solutions here as biological guanine crystals.…”
Section: The Existence Forms Of Hypoxanthine In Various Doped Guanine...mentioning
confidence: 80%
“…Excess water may not benefit the formation of α-AG crystals consisting of N 7 -guanine because the ratio of N 7 -guanine and N 9 -guanine decreases continuously with the increase of dielectric constant of solvent. 28,29 Hypoxanthine(I) was supposed to be occluded in biological guanine microplatelets mainly composed of β-AG 20,30,31 and the synthetic β-AG twinned crystals. 24,27,32 The influence of hypoxanthine on guanine crystallization was investigated by changing the molar ratios of guanine and hypoxanthine (Fig.…”
Section: Crystengcomm Papermentioning
confidence: 99%